2017
DOI: 10.4103/0975-5950.208982
|View full text |Cite
|
Sign up to set email alerts
|

Verruciform xanthoma of the tongue

Abstract: Verruciform xanthoma is a benign, soft tissue lesion occurring on the orogenital mucosa. Presentation of oral lesions can be pink, yellow, or gray raised plaque or papule with granular, papillary, or verrucous in nature. There are many theories proposed for the etiopathogenesis of verruciform xanthoma. Clinical observations may be misguiding as the lesion resembles malignant and premalignant lesions. Histopathological confirmation is essential for diagnosis and avoiding radical surgery. Once excised, the lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The literature review yielded 74 publication with a total number of 416 cases of OVX ( 1 , 4 , 9 - 73 ). With the addition of the 13 new cases of the present study, the total number of OVXs reported in the English literature is 429.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review yielded 74 publication with a total number of 416 cases of OVX ( 1 , 4 , 9 - 73 ). With the addition of the 13 new cases of the present study, the total number of OVXs reported in the English literature is 429.…”
Section: Resultsmentioning
confidence: 99%
“…Among the hypotheses suggested for its development is chronic irritation caused by trauma, which would favor epithelial cell degeneration and consequent release of lipid material, which would then be phagocyted by macrophages. 3,6,10,13,14 This hypothesis is mainly considered when the lesions in oral mucosa regions more susceptible to trauma, such as the buccal mucosa. In the present case, VX was located in the buccal mucosa, although agravating factors or trauma in the region were not identified, thus discarding this possible etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of this entity in extra-oral sites is rare and was first reported by Santa Cruz in 1979, when he reported two cases involving the vulva. [1][2][3] The pathogenesis of these lesions is unknown. Unlike its cutaneous counterpart, no disturbance of lipid metabolism, or evidence of missense mutation in exon 6 of the 3β-hydroxysteroid dehydrogenase (NSDHL) gene that plays an important role in cholesterol biosynthesis or relation to HPV has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Verruciform xanthoma is an uncommon benign mucocutaneous lesion that has a verruciform (wart-like) appearance [1]. It was first described by Shafer in the year 1971 affecting the oral mucosa [2]. The most common site for verruciform xanthoma is the oral mucosa of the gingiva and alveolar mucosa.…”
Section: Introductionmentioning
confidence: 99%